The Multilateral Trading System: Problems of Harmonization of The Multilateral and Regional Regulation of Trade and Economic Relations - Yuri Ilyich Chentukov; Elena Valerievna Bulatova (Управленческое консультирование, 2018)
The article analyzes the development of global and regional economic integration in modern conditions. The authors identified and characterized the main components of a transparent mechanism for the development of regional trade agreements in the multilateral trading system.